Adult health in the time of drought - Hoddinott, John F.; Kinsey, Bill (International Food Policy Research Institute, 2000)
This paper examines the impact of rainfall shocks on a measure of adult health, body mass, drawing on a unique panel data set of households residing in rural Zimbabwe. Controlling for individual, household, and community factors, and individual fixed, unobservable effects, we find women, but not men, are adversely affected by drought. However, these effects are not borne equally by all women. Women residing in poor households and daughters more generally appear to bear the brunt of this shock. Our results suggest that an ex ante private coping strategy, the accumulation of livestock, protects women against the adverse consequences of this shock. By contrast, we find that ex post public responses are not effective, though for several reasons we treat this finding with caution.